Design and Implementation of a Real-time Publish/Subscribe Middleware - Zheng, Pengyi (Recent Advances in Electrical & Electronic Engineering, 2019)
Background: Middleware has been widely adopted as an efficient approach to facilitate the development process of large-scale distributed systems. Although this approach can achieve simplified system design and reduced time consumption, it has a strong demand for real-time task processing and data transmitting. Traditional middleware, which lacks the real-time performance guarantee mechanism, cannot be adopted by the distributed systems with strict time restrictions. Methods: In order to meet the real-time requirements of distributed systems, the functional requirements of middleware are studied, and a real-time publish/subscribe middleware is designed and implemented in this paper. A hierarchical design is adopted to build this middleware from a model layer, a communication layer and a support layer. The middleware has the data synchronization on distributed objects, Ethernet-based publish/subscribe mechanism and the real-time performance guarantee mechanism. Results: Experiments show that the proposed middleware satisfies the needs of distributed applications, and ensures that the end-to-end data communication delay is less than 1 millisecond, which meets the real-time requirements of data transmission in distributed systems. Conclusion: In this paper, we design and implement a real-time middleware based on the publish/ subscribe mechanism.
Keywords: guarantee mechanism